2017
DOI: 10.1039/c7ta06674k
|View full text |Cite
|
Sign up to set email alerts
|

CO2electoreduction reaction on heteroatom-doped carbon cathode materials

Abstract: This highlight summarizes the recent developments of heteroatom-doped carbon cathode catalysts for CERR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 48 publications
0
44
0
1
Order By: Relevance
“…However, carbon materials generally possess negligible inherent activity for the electroreduction of CO 2 , due to the absence of active sites. Heteroatom doping into the carbon framework stands out as an effective tuning knob for improving the activity of CO 2 reduction, by modulating the electronic properties of adjacent carbons, e.g., charge and spin density …”
Section: Electrocatalysts For Selectively Reducing Co2 To Comentioning
confidence: 99%
“…However, carbon materials generally possess negligible inherent activity for the electroreduction of CO 2 , due to the absence of active sites. Heteroatom doping into the carbon framework stands out as an effective tuning knob for improving the activity of CO 2 reduction, by modulating the electronic properties of adjacent carbons, e.g., charge and spin density …”
Section: Electrocatalysts For Selectively Reducing Co2 To Comentioning
confidence: 99%
“…For instance, S‐doped porous carbon (CPSN) was demonstrated to be able to generate both CO and CH 4 with a FE CO of 11.3% and FE CH4 of 0.2%, respectively, at an applied potential of −0.99 V . Moreover, Liu et al reported that phosphorous‐doped carbon could selectively reduce CO 2 to CO with FE CO of 81% at −0.9 V with partial j CO of −4.9 mA cm −2 . The DFT calculations indicate that the PC bonding configuration is responsible for higher reactivity toward the adsorption of radical intermediates and this allows the attainment of high FE CO .…”
Section: Active Sites In Carbon‐based Catalystsmentioning
confidence: 99%
“…For example, pyridinic nitrogen has been widely proved to activate graphene, carbon nanotube, and nanodiamond . Boron, phosphorus, and fluorine activating strategies have also been proved successfully, with an example of fluorine dopant improving the j CO with 250,000 times enhancement over the commercial carbon material . This exciting results can be explained with the reason that the fluorine dopant could activate more than one carbon atoms among several bonds as the highly active reaction sites (Figure ).…”
Section: Recent Progress Towards Practical Electrochemical Co2 Splittingmentioning
confidence: 99%